Comparative Profitability Analysis of Watermelon and Pepper Production in Danko-Wasagu Local Government Area of Kebbi State, Nigeria - M.D, Baba; Yelwa, J.M; Yakubu, G; Sanchi, I.D (Review of Knowledge Economy, 2014)
This research was carried out to examine the comparative profitability of watermelon and pepper production in Danko-Wasagu Local Government Area of Kebbi State, Nigeria. Proportionate random sampling technique was used to select sixty (60) watermelon producers and sixty (60) pepper producers. Thus, a total of one hundred and twenty respondents constitute the sample size for the study. Interview schedule was used to collect primary data from the respondents. The data collected were analyzed using percentage, farm budgeting technique and t-test statistics. Result revealed that majority of watermelon (75%) and pepper (71.6%) producers are males and that 56.67% of watermelon and 48.33% of pepper producers are within the age bracket of 31 – 40 years. Findings also revealed that net farm income for watermelon and pepper production were N 30, 946 and N 19, 592 per hectare, respectively. This therefore, indicated that both enterprises were profitable, but watermelon is more profitable than pepper. The rate of return on investment per hectare was estimated at 55.1% and 45.3% for watermelon and pepper, respectively. Hence, for every naira invested in watermelon and pepper production, the producers generated 55.1% and 43.5% as profit. However, theft, pest and diseases are the most severe problems faced by watermelon and pepper producers in the study area. It is therefore, recommended that adequate security measures and prompt pest and disease control measures will improve the overall productivity of both watermelon and pepper production which will in turn generate more income for the farmers.